Konflik Kepentingan dalam Proses Pergantian Antar Waktu Kepala Desa Labangka, Kecamatan Labangka, Kabupaten Sumbawa pada Tahun 2023 - Dianto; Jasardi Gunawan (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study discusses the conflict of interest in the Interim Replacement (PAW) process of the Head of Labangka Village, Labangka District, Sumbawa Regency in 2023. The PAW process has been implemented in accordance with the provisions of Law Number 6 of 2014 concerning Villages, Minister of Home Affairs Regulation Number 112 of 2014, and Sumbawa Regent Regulation Number 49 of 2022. However, its implementation experienced polemics after the elected candidate, Jumaidi, had his appointment revoked based on a court decision because he did not meet the requirements. Nevertheless, the PAW process as a whole remains valid and has not been canceled. The problem arose when the Regent of Sumbawa did not follow up on the election results and instead appointed an acting village head through Decree Number 214 of 2025, which was deemed to be contrary to laws and court decisions. The appointment was also considered to violate the Village Law and Constitutional Court Decision Number 107/PUU-XXII/2024. This study recommends that the Regent immediately inaugurate the candidate with the second-highest number of votes or hold a revote without Jumaidi's involvement. This is crucial to ensure legal certainty, prevent vacancies, and uphold the principles of democracy and the rule of law in village governance.